2014
DOI: 10.1080/0305215x.2014.971779
|View full text |Cite
|
Sign up to set email alerts
|

Towards the optimal design of an uncemented acetabular component using genetic algorithms

Abstract: Aseptic loosening of the acetabular component (hemispherical socket of the pelvic bone) has been mainly attributed to bone resorption and excessive generation of wear particle debris. The aim of this study was to determine optimal design parameters for the acetabular component that would minimize bone resorption and volumetric wear. Three-dimensional finite element models of intact and implanted pelvises were developed using data from computed tomography scans. A multi-objective optimization problem was formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…6,37,38 Contact pressure and sliding distance at each element of contact surface were measured for each load cases (comparison between loading and unloading conditions) and corresponding values were considered for wear depth calculation as similar to earlier studies. 37,39 Validation of the FE model…”
Section: Wear Depth Assessmentmentioning
confidence: 99%
“…6,37,38 Contact pressure and sliding distance at each element of contact surface were measured for each load cases (comparison between loading and unloading conditions) and corresponding values were considered for wear depth calculation as similar to earlier studies. 37,39 Validation of the FE model…”
Section: Wear Depth Assessmentmentioning
confidence: 99%
“…Apart from the contact pressure, the micromotion between implants is also an important parameter to quantify the wear in the cemented acetabular cup. 4749 The high (maximum) value of contact pressure and micromotion in this study was found for UHMWPE-CoCrMo compared to other implant material combinations (Figure 11). These values further increased with the increase in the patient’s bodyweight and decrease in bone quality.…”
Section: Discussionmentioning
confidence: 62%
“…The detailed descriptions of the FE modeling procedure of the pelvic bone was presented in earlier studies. [16][17][18][19][20] The generation procedure of the FE model of the pelvic bone was validated and verified experimentally. 21,22 Both intact and implanted pelvic bone model were generated to evaluate causes of failure of the cemented polyethylene acetabular component.…”
Section: Methodsmentioning
confidence: 99%
“…The Young's Modulus of the UHMWPE acetabular component and cement mantle were considered as 1.174 GPa and 2 GPa, respectively and the Poisson's ratio for each of these materials was taken as 0.4 and 0.33. 6,20 The spherical femoral head was made of CoCrMo alloy and for this material, Young's modulus was considered as 210 GPa and Poisson's ratio of 0.3. 16…”
Section: Materials Propertiesmentioning
confidence: 99%